CRYOPRESERVATION OF LEISHMANIA DONOVANI PROMASTIGOTES AT -80°C - E. Kaneva (Trakia Journal of Sciences)
Visceral leishmaniasis (VL) is one of the important parasitic diseases caused by the obligate intracellular protozoan parasite of Leishmania donovani complex. The disease is associated with severe morbidity and is fatal if left untreated. Human VL is rare in Bulgaria, but local cases are registered annually in the country. Diagnosis of the disease is based on clinical and epidemiological data and the different laboratory methods for ethiological diagnosis. Isolation of the causative agent through cultural methods, allows to make an extremely accurate diagnosis, but require time and cost of materials. Cryopreservation of isolated parasites allows their keeping for a long time and recovery in need of subsequent immunological and molecular analyzes. The described and optimized cryopreservation method of Leishmania species promastigotes in laboratory conditions is easily feasible and reliable and can be used for long-term storage of these parasites without changing their viability and biological characteristics.